(untitled) (Global Journal of Human-Social Science, 2016)
Three of the world s greatest challenges over the coming decades will be biodiversity loss climate change and water stress World Bank 2008 Global climate change is undoubtedly the most pervasive complex and challenging of the global environmental issues facing contemporary society and it affects all aspects of development The effects of climate change are local and vary among systems sectors and regions Although many natural and economic sectors will be affected by climate change impacts on agriculture and water availability will have the greatest potential to negatively affect the livelihoods of the poor in rural areas as well as national economic growth in the least-developed countries especially for the people of sub-Saharan Africa SSA Roetter et al 2002 The high dependence of the economies and rural people of SSA upon rain fed agriculture the prevalence of poverty and food insecurity and limited development of institutional and infrastructural capacities makes coping with natural climate variability a perennial challenge This challenge is being magnified by global climate change Cline 2007 Lobell et al 2008 Expanding agriculture leads to habitat loss and fragmentation drainage of wetlands and impacts on freshwater and marine ecosystems through sedimentation and pollution and is one of the greatest threats to biodiversity worldwide World Bank 2008